PERANAN MOTIVASI KERJA UNTUK MENINGKATKAN KINERJA PNS BAGIAN TATA USAHA PADA BALAI BESAR PENDIDIKAN DAN PELATIHAN KESEJAHTERAAN SOSIAL REGIONAL IV KALIMANTAN - Sri Mulyani; Diana Hayati; Erma Damai Yanti (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2020)
Abstract, This research aims to determine the role of work motivation in improving the performance of civil servants in the administration section of the IV Kaliamantan regional social welfare training and education center. The method used in this research is descriptive qualitative method. The subjects in this study were all 11 Civil Servants of the Regional IV Kalimantan Social Welfare Training and Education Center. The conclusion of this research is that all this time the work motivation given to civil servants in the administration division is still lacking, causing the performance of civil servants to decline which is marked by an understanding of the wrong target amount of workload. Lack of socialization is also one of the causes of low performance results because with low socialization, there is also a low understanding of the determination of PNS Performance Targets (SKP) for the assignments of each PNS.